A comparative survey on recovery performance of thermo-electric generator recovery system with air cooling during warming process of internal combustion gasoline engines - Mehmet Akif Kunt (Pamukkale University Journal of Engineering Sciences, 2018)
Thermoelectric generators are long-life electricity generators that operate according to the Seebeck thermoelectric effect and produce DC voltage by utilizing the temperature difference on hot and cold surfaces, without moving parts. The ability to generate electricity directly in any situation where the temperature difference between the surfaces of the thermoelectric modules arises makes it possible to generate electricity from the first time in the exhaust systems of the internal combustion engines. It is very important to examine the recovery of the thermoelectric generators in the heating process in the internal combustion engines due to the reduced generator efficiency at low revs. In this study, thermoelectric generators were used to provide exhaust heat recovery in heating process of an internal combustion gasoline engine, electrical gains obtained at three different temperature averages were investigated and experimental and simulated results were compared. A maximum ΔT = 165 °C temperature difference was obtained between the module surfaces. In the experiments performed, ΔT = 165 °C, RL = 10 Ω load resistance, maximum 6.75 V voltage, 0.65 A current is obtained. Experimental and simulation results are generally in coherence.